2019
DOI: 10.5204/ijcjsd.v8i2.1027
|View full text |Cite
|
Sign up to set email alerts
|

Right to Sexual Autonomy of Children—Implications of the UNCRC upon the Indian Law on the Age of Consent

Abstract: This article discusses the implications of sexual autonomy of children under international child rights regime upon Indian law. Indian general criminal law defining the offence of rape and a special statute defining different types of child sexual assault led to the inference that the current age of consent is 18 years. Despite statutory prohibition of child marriages in India, the general criminal law contains an explanatory provision exempting the rape of a married woman above the age of 15. The Supreme Cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Literature has shown that child marriages are most common in rural areas, with poverty, cultural traditions, and values based on patriarchal norms cited as fundamental reasons for the practice [ 12 , 13 , 14 ]. The low level of education of girls, the lower status of girls, the consideration of girls as a financial burden, social customs, and a mixture of these causes result in the imprisonment of girls in marriage without consent [ 15 ]. Montazeri et al [ 14 ] also reported that freedom from undesirable and rigid rules of parents, the low authority of girls, and lack of power to make a decision are also some notable consequences of child marriage.…”
Section: Introductionmentioning
confidence: 99%
“…Literature has shown that child marriages are most common in rural areas, with poverty, cultural traditions, and values based on patriarchal norms cited as fundamental reasons for the practice [ 12 , 13 , 14 ]. The low level of education of girls, the lower status of girls, the consideration of girls as a financial burden, social customs, and a mixture of these causes result in the imprisonment of girls in marriage without consent [ 15 ]. Montazeri et al [ 14 ] also reported that freedom from undesirable and rigid rules of parents, the low authority of girls, and lack of power to make a decision are also some notable consequences of child marriage.…”
Section: Introductionmentioning
confidence: 99%
“…Paul, 2019). It also curtails the sexual and reproductive autonomy of child brides, wherein the right to choose the timing, number and spacing of birth is completely taken away from them (Barman et al, 2020;Castilla, 2018;Framework, n.d.;Mathew, 2019).…”
Section: Introductionmentioning
confidence: 99%